2020
DOI: 10.1002/ptr.6734
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rd therapy improves histological and functional recovery in a rat model of inflammatory bowel disease

Abstract: Ginsenoside Rd (GRd) is a biologically active component of ginseng that stimulates the proliferation of endogenous stem cells. The objective of our research was to evaluate the utility of GRd in gastrointestinal mucosal regeneration in a rat model of inflammatory bowel disease (IBD) and to clarify whether GRd exerts its pharmacological effects by modulating endogenous intestinal stem cells. The IBD rat model was established via subcutaneous injection of indomethacin, and 10, 20, or 40 mg/kg GRd or an equal vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…TGF-β signaling is recognized as a vital anti-inflammatory signal transduction pathway. In vivo experimental studies suggest that ginsenosides enhance intestinal mucosal epithelial cell proliferation and modulate the immunocyte differentiation as well as inflammatory factor production, thereby efficiently mitigating the IBD symptoms (Yang et al, 2020). Yang reported that ginsenoside Rd could alleviate the TNBS-induced UC symptoms in animals by enhancing the oxidation resistance of injured colons and suppressing neutrophil infiltration (Yang et al, 2012a).…”
Section: Terpenoidsmentioning
confidence: 99%
“…TGF-β signaling is recognized as a vital anti-inflammatory signal transduction pathway. In vivo experimental studies suggest that ginsenosides enhance intestinal mucosal epithelial cell proliferation and modulate the immunocyte differentiation as well as inflammatory factor production, thereby efficiently mitigating the IBD symptoms (Yang et al, 2020). Yang reported that ginsenoside Rd could alleviate the TNBS-induced UC symptoms in animals by enhancing the oxidation resistance of injured colons and suppressing neutrophil infiltration (Yang et al, 2012a).…”
Section: Terpenoidsmentioning
confidence: 99%
“…Ginsenoside Rd was treated to evaluate its effect on gastrointestinal mucosal regeneration with an inflammatory bowel disease (IBD) rat model. [ 40 ]. We found that Lentilactobacillus buchneri URN103L with β-glucosidase activity, isolated from the fermentation of medicinal plants, has the potential to convert ginsenoside Rb1 into Rd and Rg3.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, relevant studies reported that ginsenosides, the main active components of Panax ginseng, had anti-inflammatory and immunomodulatory effects on IBD, including improving body weight, decreasing disease activity index (DAI), and the index of colonic weight and body weight or colonic length, restoring pathological damage in colonic mucosa, and reducing microscopic, and macroscopic injury scores [ 40 ]. In vivo experiments showed that ginsenosides not only promoted the proliferation of intestinal mucosal epithelium, but also regulated the differentiation of immune cells and the secretion of inflammatory mediators; thus, effectively relieving the symptoms of IBD [ 41 ]. In vitro cell experiments showed that ginsenosides could effectively inhibit HT-29 cells to secrete pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) under lipopolysaccharide (LPS) stimulation [ 6 ].…”
Section: Ginsenosidesmentioning
confidence: 99%